From the cradle to the clinic: VEGF in developmental, physiological, and pathological angiogenesis. - Harry, L; Paleolog, E (2003)
Formation of new blood vessels, which is fundamental in embryonic development, occurs through a combination of angiogenesis and vasculogenesis. Angiogenesis also plays a vital role postnatally, especially in reparative processes such as wound and fracture healing. Some of these events, especially in fracture healing, recapitulate processes observed in developmental angiogenesis. However, dysregulated angiogenesis is well documented to underlie a number of pathological disorders, including rheumatoid arthritis (RA). The vascular endothelial growth factor (VEGF)/VEGF receptor system is the best characterized regulator of angiogenesis. VEGF is expressed in a range of cells in response to soluble mediators (such as cytokines and growth factors), cell-bound stimuli (such as CD40 ligand), and environmental factors (such as hypoxia). As a consequence, this molecule is vital in the modulation of physiological and pathological angiogenesis. This review will focus in particular on the role played by VEGF in embryogenesis and skeletal growth, in fracture healing (in which increased angiogenesis is likely to be beneficial in promoting union), and in RA (in which excessive angiogenesis is thought to play a significant role in disease pathogenesis). In the not-too-distant future, targeting VEGF may prove to be of benefit in the treatment of diseases associated with excessive or aberrant angiogenesis, such as malignancies and RA.